Pengembangan Model Latihan Pola Penyerangan Permainan Bola Basket pada Ekstrakurikuler di SMAN 21 Palembang. - Oktariansyah, M. ilham; Kumbara, Hengki; Mahendra, Agung (Peneliti.net, 2023)
The development of a training model for attacking patterns in basketball games during extracurricular activities at SMAN 21 Palembang was the focus of this research. The exploration strategy utilized in this examination is Innovative work (R and D) from Borg and Gall. Information assortment was done utilizing a survey, an exploration test of b-ball extracurricular understudies at SMAN 21 Palembang to direct a restricted preliminary of 10 extracurricular understudies. Investigation of examination information utilizing a viable poll. The validation of the initial product's feasibility by material experts yielded this study's results, which met the criterion